The Influence Of Political And Cultural Leadershipon The Performance Of Employees Of The Bengkulu Provincial House Of Representatives Secretariat - Aswar Aswar; Kresnawati Kresnawati; Dodi Hardinata (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of political leadership and work culture on the performance of employees at the Bengkulu Provincial DPRD Secretariat. The research approach used was quantitative with multiple linear regression. The study population included all employees at the Bengkulu Provincial DPRD Secretariat, with a sample size of 74 respondents obtained through saturated sampling. Data collection was conducted using a questionnaire with a five-point Likert scale, while data analysis was performed using SPSS. The results showed that political leadership had a positive and significant effect on employee performance, meaning that the more effective the political leadership, the higher the employee performance. Meanwhile, work culture had a positive but insignificant effect on employee performance, thus concluding that work culture values ​​have not been fully and consistently implemented by all employees. Simultaneously, political leadership and work culture had a significant effect on employee performance, with a coefficient of determination (R²) of 0.150, indicating that these two variables explain 15% of the variation in employee performance, with the remainder influenced by factors outside this study. This finding emphasizes the importance of strengthening participatory political leadership and establishing a professional and integrity-based work culture to improve employee performance within the Bengkulu Provincial DPRD Secretariat.